Role of LTA4H Polymorphism in Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome Occurrence and Clinical Severity in Patients Infected with HIV - Narendran, Gopalan (PLoS One, 2016)
BACKGROUND: Paradoxical tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is an inflammatory phenomenon complicating HIV management in coincidental tuberculosis (TB) infection, upon immune reconstitution driven by antiretroviral therapy (ART). Leukotriene A4 hydroxylase (LTA4H), an enzyme which converts LTA(4) to LTB(4), regulates the balance between the anti-inflammatory lipoxins and pro-inflammatory LTB(4), with direct implications in TB-driven inflammation. In humans, a single nucleotide polymorphism (SNP) in the LTA4H promoter which regulates its transcriptional activity (rs17525495) has been identified and described to impact clinical severity of TB presentation and response to corticosteroid therapy. Notably, the role of LTA4H on TB-IRIS has not been previously evaluated. Here, we performed an exploratory investigation testing the association of LTA4H polymorphism with respect to frequency of TB-IRIS occurrence and severity of TB-IRIS presentation in HIV-TB co-infected individuals. METHODS: Genotypic evaluation of the LTA4H enzyme from available samples was retrospectively correlated with clinical data captured in case sheets including IRIS details. The cohort included patients recruited from a prospective cohort study nested within a randomized clinical trial (NCT0933790) of ART-naïve HIV+ patients with newly diagnosed rifampicin sensitive pulmonary TB in South India. Frequency of the wild type genotype (CC), as well as of the mutant genotypes (CT or TT) in the IRIS and non-IRIS patients was estimated. Comparative analyses were performed between wild genotype (CC) and the mutant genotypes (CT or TT) and tested for association between the LTA4H polymorphisms and IRIS incidence and clinical severity. RESULTS: A total of 142 eligible ART-naïve patients were included in the analyses. Eighty-six individuals exhibited the wild genotype (CC) while 56 had mutant genotypes (43-CT and only 13-TT). Variant allele frequency was 0.23 and 0.26 in non-IRIS group and in IRIS group, respectively. Upon ART initiation, 51 patients developed IRIS while 91 did not. IRIS incidence was 34% and 37% in the wild (CC) and mutant type (CT/TT), respectively (p = 0.858) with a higher frequency of severe IRIS presentation in the mutant genotype group compared to the wild type genotype (p = 0.0006). A logistic regression model confirmed the association between the presence of CT/TT genotypes and occurrence of severe IRIS. Corticosteroid therapy successfully resolved IRIS in all cases irrespective of the LTA4H genotype. CONCLUSION: A higher incidence of severe IRIS among patients with mutant LTA4H genotypes (CT and TT) was observed compared to the wild type, despite similar IRIS incidence and immune restoration in both groups. Steroids were effective in alleviating IRIS in all the genotypes.